Assessment of heavy metal pollution in Red River surface sediments, Vietnam. Issue 1 (15th December 2016) - Nguyen, Thi Thu Hien; Zhang, Weiguo; Li, Zhen; Li, Jie; Ge, Can; Liu, Jinyan; Bai, Xuexin; Feng, Huan; Yu, Lizhong
Abstract: Surface sediment samples were collected from upstream down to the subaqueous delta of the Red River in Vietnam to assess heavy metal pollution. Sediment Cr and V concentrations are strongly correlated with Al, Fe, Mn and total organic carbon concentrations, as well as particle size, suggesting that these two metals are derived primarily from natural sources and enriched in the fine fraction of sediments. In contrast, Cu, Cd, Pb, Ni and Zn concentrations show weaker correlations with particle size, with very high concentrations observed at several sites in the upper reach of the river, pointing to anthropogenic input as a possible source of these heavy metals. Enrichment factors (EF) of Cu, Cd, Pb, Ni and Zn suggest that heavy metal pollution is present in sediments with significantly high values in the upstream. The data analysis indicates that Cd, Cu and Pb are the dominant pollutants in the Red River, with their concentrations reaching moderate to serious pollution levels. Highlights: Heavy metal pollution in sediments along the Red River is assessed. Cr and V have a dominant natural source. Cd, Cu and Pb are heavily polluted in the upstream. Zn and Ni display a mixed natural and anthropogenic sources.